Mutations d’une idée de théâtre national: le Teatro Nacional D. Maria II hier et aujourd’hui - Brilhante, Maria João (2018)
This text aims to identify some of the issues concerning how the national character of the Teatro Nacional D. Maria II has been created from the initial project, designed by Almeida Garrett according to the liberal political programme in Portugal, to the changes made under different political, socio-cultural and artistic contexts along its existence. The TNDM II was born in the frame of the emergence of the Nation-State and its identity has been affected by the transformations associated with this fact. Our purpose is double: to understand the continuous framing of its relationship with the State, considering the strategies developed to guarantee its activity; to find out what does it mean to be a national theatre, today, in Portugal.